Strengthening of reinforced concrete structures using externally-bonded FRP composites in structural and civil engineering - Hollaway, L.; Leeming, M. B. (CRC Press ; Woodhead Pub., 1999)
This book presents a detailed study of the flexural strengthening of reinforced and prestressed concrete members using fibre reinforced polymer composite plates. The authors also discuss plate bonding onto other engineering materials such as steel and cast iron. The book has been designed for practising civil and structural engineers seeking to understand the principles and design technology of plate bonding, and for final year undergraduates and postgraduate engineers studying the principles of highway and bridge engineering and structural engineering.
Keywords: Fiber-reinforced concrete.; Fibrous composites.; Buildings, Reinforced concrete.; Concrete beams.; elektronické knihy; electronic books